Green Worlds of Renaissance Venice - Cranston, Jodi (Penn State University Press, 2019)
From celebrated gardens in private villas to the paintings and sculptures that adorned palace interiors, Venetians in the sixteenth century conceived of their marine city as dotted with actual and imaginary green spaces. This volume examines how and why this pastoral vision of Venice developed. Drawing on a variety of primary sources ranging from visual art to literary texts, performances, and urban plans, Jodi Cranston shows how Venetians lived the pastoral in urban Venice. She describes how they created green spaces and enacted pastoral situations through poetic conversations and theatrical performances in lagoon gardens; discusses the island utopias found, invented, and mapped in distant seas; and explores the visual art that facilitated the experience of inhabiting verdant landscapes. Though the greening of Venice was relatively short lived, Cranston shows how the phenomenon had a lasting impact on how other cities, including Paris and London, developed their self-images and how later writers and artists understood and adapted the pastoral mode. Incorporating approaches from eco-criticism and anthropology, Green Worlds of Renaissance Venice greatly informs our understanding of the origins and development of the pastoral in art history and literature as well as the culture of sixteenth-century Venice. It will appeal to scholars and enthusiasts of sixteenth-century history and culture, the history of urban landscapes, and Italian art.